Labview-based FPGA implementation of sensor data acquisition for human body motion measurement - Tukiran, Zarina; Ahmad, Afandi; Muharam, Azlan; Ja’afar, Noor Huda; Mohd Nadzri, Muhammad Muzakkir (Penerbit UTHM, 2020)
Measuring body motion is crucial to identify any abnormal neuromuscular control, biomechanical disorders and injury prevention in various applications such as rehabilitation [1], [2], sport science [3],[4], surveillance [5], and virtual reality [6]. The measurement can be performed by using vision-based [7]-[9] and non-vision-based [10]-[12] systems. The vision-based systems use optical sensors, such as cameras, to track human movements. Whilst the non-vision-based systems employ sensor technology, such as magnetic, and inertial, attached to the human body to collect human movement information. The vision-based systems offer a more accurate system, however, in this work, the non-vision-based systems are employed as it offers portability as one of the advantages.